Jak2 Tyrosine Kinase: A Potential Therapeutic Target for AT1 Receptor Mediated Cardiovascular Disease - Peter P. Sayeski; Annet Kirabo (MDPI AG, 2010)
Patients with hypertension often manifest a dysregulated renin-angiotensin-aldosterone system (RAAS). Most of the available treatment approaches for hypertension are targeted towards the RAAS including direct renin inhibition, ACE inhibition, angiotensin II type 1 receptor (AT1-R) blockade, and aldosterone receptor antagonism. The Jak2 signaling pathway is intricately coupled to the AT1-R signaling processes involved in hypertension. Here, we review the involvement of Jak2 in the pathogenesis of hypertension, and its potential as a therapeutic target for treatment of AT1-R mediated cardiovascular disease. Jak2 may provide a rational therapeutic approach for patients whose blood pressure is not controlled by standard therapies.